Sarkasme Dalam Stand-up Comedy di Konten Media Sosial Komika Lokal Gorontalo di Kawasan Teluk Tomini - Balango, Mery (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2025)
Sarcasm is one of the of figurative language elements defined as opposite speech with its actual meaning. This study aims to describe how a comedian conveys his ideas about a joke by using sarcasm in video content. This study used a qualitative descriptive method, because of the purpose of this study was to describe the sarcastic words used by a comedian in a video, so qualitative research with a descriptive method was the most appropriate method. The results show that local stand-up comedian from Gorontalo City on YouTube uses sarcastic humor for various reasons, including creating a communication with listeners, increasing the effectiveness of their jokes, resilient to different audiences, and enriching the overall entertainment value. This strategy allows comedians to make their jokes more memorable and impactful, then ultimately providing a truly entertaining and engaging comedy experience.